ÓZLESTIRMEWSHI OQÍWSHÍLARDÍŃ KOGNITIV TARAWÍNÍŃ PSIXOLOGIYALÍQ ÓZGESHELIKLERI - Sh.Sherimbetova, Z. (FAN va JAMIYAT, 2024)
The article talks about the psychological characteristics of the cognitive of non-assimilating students. Concepts about the characteristics of students’ cognitive processes are presented.